Energía a partir de residuos sólidos urbanos, caso parroquia Limoncocha en la Amazonía ecuatoriana (Tema Central) - Coral Carrillo, Katty Verónica (2021)
The solid urban waste overproduction (MSW) affects both the environment and human health; the Limoncocha parish, located in the Ecuadorian Amazon Region is no exception, disposing its waste in a garbage dump located in Shushufindi or taking its own measures, disposing the waste in household pits or by burning in the open air. The study is part of an investigation on the chemical, physical and biological properties of MSW, properties like, its use as a potential source of energy using energy harvesting processes. The concentrations of food waste, plastics, paper, cardboards and in a smaller quantity, wood and textiles are characterized. The possibility of energy use was evaluated through incineration among higher (PCS) and lower (PCI) caloric power that could be recovered, obtaining values between 3154 and 4560 kcal / kg for PCS and 3100 and 4436 kcal / kg for PCI. The results indicate that 92 % by weight contains potential energy greater than 3100 kcal / kg and can be subjected to energy use processes. In order to be used, it is necessary to create a community with the surrounding populations since the waste flow that is equivalent to 1.7 t / day is insufficient to implement said system individually.